Reshaping lipid metabolism with long-term alternate day feeding in type 2 diabetes mice - Eleni Beli; Yuanqing Yan; Leni Moldovan; Todd A. Lydic; Preethi Krishman; Sarah A. Tersey; Yaqian Duan; Tatiana E. Salazar; James M. Dominguez; Dung V. Nguyen; Abigail Cox; Sergio Li Calzi; et al. (npj Metabolic Health and Disease)
Abstract Strategies to improve metabolic health include calorie restriction, time restricted eating and fasting several days per week or month. These approaches have demonstrated benefits for individuals experiencing obesity, metabolic syndrome, and prediabetes. However, their impact on established diabetes remains incompletely studied. The chronicity of type 2 diabetes (T2D) requires that interventions must be undertaken for extended periods of time, typically the entire lifetime of the individual. In this study, we examined the impact of intermittent fasting (IF), with an every-other-day protocol for a duration of 6 months in a murine model of T2D, the db/db (D) mouse on metabolism and liver steatosis. We compared D-IF mice with diabetic ad-libitum (AL; D-AL), control-IF (C-IF) and control-AL (C-AL) cohorts. We demonstrated using lipidomic, microbiome, metabolomic and liver transcriptomic studies that chronic IF improved carbohydrate utilization and glucose homeostasis without weight loss and reduced white adipose tissue inflammation and significantly impacted lipid metabolism in the liver. Microbiome studies and predicted functional analysis of gut microbiota showed that IF increased beneficial bacteria involved in sphingolipid (SL) metabolism. The metabolomic studies showed that oxidation of lipid species and ceramide levels were reduced in D-IF compared to D-AL. The liver lipidomic analysis and liver microarray confirmed a reduction in overall lipid content in D-IF mice compared to D-AL mice, especially in the feeding state as well as an overall reduction in oxidized lipids and ceramides. These studies support that long-term IF can improve glucose homeostasis and dramatically altered lipid metabolism in the absence of weight loss.